2016
DOI: 10.1590/2179-8087.127715
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição Espacial e Cobertura de Vegetação das Tipologias de Áreas Verdes de Curitiba, PR

Abstract: RESUMOA vegetação nas cidades desempenha funções ecológicas, estéticas e sociais que melhoram a qualidade de vida urbana. Para que essas funções sejam eficientes é necessário a realização de estudos quantitativos e qualitativos das áreas verdes (AVs) na cidade. O objetivo do estudo foi identificar a cobertura de vegetação presente nas diferentes tipologias de AVs nas unidades administrativas de Curitiba, PR, bem como analisar sua configuração espacial ao longo da paisagem urbana. A cobertura de vegetação foi i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
(1 reference statement)
0
8
0
5
Order By: Relevance
“…The irregular distribution of vegetation, in the ways of the city of Goiânia, was also observed in some North American and Chinese cities (Wolchet al, 2014), and in the city of Curitiba (Grise et al, 2016). Hussein et al ( 2018) observed, in their analyzes, in the city of Erbil, Iraq, that the newly built districts and the districts furthest from the central area registered greater vegetation coverage compared to the older and consolidated districts.…”
Section: Resultsmentioning
confidence: 88%
“…The irregular distribution of vegetation, in the ways of the city of Goiânia, was also observed in some North American and Chinese cities (Wolchet al, 2014), and in the city of Curitiba (Grise et al, 2016). Hussein et al ( 2018) observed, in their analyzes, in the city of Erbil, Iraq, that the newly built districts and the districts furthest from the central area registered greater vegetation coverage compared to the older and consolidated districts.…”
Section: Resultsmentioning
confidence: 88%
“…The central-northern region of the city of Curitiba was indicated to be the most relevant for the occurrence of Ocotea odorifera due to the fact that the north region concentrates the highest altitudes of approximately 1,000 m and slopes, in addition to soils groups Latosols and Cambisols, indicated by Martins (2016) as preferred by the species. Besides these aspects, according to Grise, Biondi and Araki (2016b), the Boa Vista and Matriz regions, located in the north of the city, have the largest amounts of protected areas in the municipality. Thus, the results corroborate the places where the individuals of the species were recorded, and those with the highest probability of species' distribution are located closer to the northern limit of Curitiba and at higher altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Essas tipologias de área verde protegida foram escolhidas por possuírem as maiores áreas de fragmentos de vegetação remanescente do município (Grise et al 2016b); por oferecerem maiores possibilidades de conservação da espécie em relação às áreas particulares comuns, uma vez que já se encontram com os seus usos consolidados regidos por legislações específicas (Curitiba 2000; e por apresentarem, em geral, menos impactos antrópicos. No entanto, como existem outras tipologias de áreas verdes protegidas no município e que não se enquadram nos referidos requisitos, optou-se pelo termo Áreas Verdes Protegidas Selecionadas (AVPS).…”
Section: Procedimentos Metodológicosunclassified
“…A região centro-norte de Curitiba contém a maior quantidade de áreas verdes protegidas do município (Grise et al 2016a;2016b), podendo fornecer melhores condições para a proteção dos atuais indivíduos de O. odorifera. Além disso, essas áreas protegidas podem ser utilizadas para incrementar a regeneração natural da espécie e plantios de reintrodução.…”
Section: Classeunclassified